Investigation of host-specificity of phytopathogenic fungi isolated from woody plants - Zabiák, Andrea; Károlyi, Györk Milán; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2020)
Host-specificity is an important characteristic of fungal pathogens. Changing climate could create more appropriate environmental conditions for phytopathogens, thus formerly host-specify fungi could be able to colonize new hosts. Noxious plant pathogen fungi, which can infect several plant species are well-known worldwide. These genera may expand their range of hosts because of the appearance in new geographic areas due to climate change. This new exposure can result in serious problems in agriculture because of the lack of immunity. The susceptibility of apple tree was studied through testing pathogenicity in vitro with species isolated from walnut twigs and nuts, and identified by ITS sequences. Three of four tested species, Botryosphaeria dothidea, Diaporthe eres and Diplodia seriata colonized and necrotized the infected apple branches, while Juglanconis juglandina was not able to infect the twigs. Members of Botryosphaeriaceae were the most virulent, causing the largest lesions in the fastest way. This experiment draws attention to the threat of new host-pathogen connections, which can arise because of the favourable weather conditions and can spread between neighbouring cultures.